Fluid overload-associated large B-cell lymphoma: two case report and review of literature - Chang, Liudi; Yang, Zhaobo; Yang, Cuicui; Wang, Yuxiao; Li, Dan; Wang, Hui; Zang, Lanlan; Zhang, Yuanyuan (Frontiers in Oncology, 2025)
BackgroundFluid overload-associated large B-cell lymphoma (FO-LBCL) is an exceptionally rare lymphoma characterized by predominant involvement of serous body cavities—such as the pleura, peritoneum, and pericardium—in the absence of a solid tumor mass. Its low incidence and nonspecific clinical presentation, which often includes symptoms like dyspnea due to effusion, contribute to diagnostic challenges in early stages. This study aims to address current gaps in the understanding of FO-LBCL by reporting two new cases and reviewing the clinical features, treatment regimens, and outcomes of 57 documented patients. Furthermore, through a detailed analysis of FO-LBCL characteristics, this work discusses relevant differential diagnoses and potential treatment strategies.MethodsA literature search of PubMed and Web of Science was performed using the following search queries: (1) “Fluid overload-associated large B-cell lymphoma” OR “FO-LBC”; (2) “Human herpesvirus 8-unrelated” AND “effusion lymphoma”; (3) “HHV8-unrelated” AND “effusion lymphoma”.ResultsThis study included a total of 57 patients. Fluid accumulation most commonly affected the pleural cavity (84.2%), followed by the pericardial (31.6%) and peritoneal (21.1%) cavities. The predominant clinical manifestation was dyspnea (55.8%). Chemotherapy was the primary treatment modality (56.1%), with the R-CHOP regimen representing the most commonly administered protocol. CD20 expression was the most significant favorable prognostic factor (P = 6×10-7). Other factors associated with improved survival included the absence of CD138 expression (P = 0.0009), age ≥ 65 years (P = 0.0015), LDH ≤ 500 U/L (P = 0.0064), the presence of pleural effusion (P = 0.0099), and CD79a expression (P = 0.0411). Treatment with rituximabcontaining chemotherapy regimens was also a significant favorable factor (P = 0.0036).ConclusionsFO-LBCL often presents with dyspnea caused by fluid effusion. Routine laboratory tests typically show no significant abnormalities, making timely pathological examination essential for a definitive diagnosis. Clinicians should enhance their understanding of FO-LBCL characteristics to improve early diagnostic accuracy. It is crucial to select appropriate treatment strategies based on prognostic factors.